2008
DOI: 10.1084/jem.20080397
|View full text |Cite
|
Sign up to set email alerts
|

Human interleukin 17–producing cells originate from a CD161+CD4+ T cell precursor

Abstract: We demonstrate that CD161 is a highly up-regulated gene in human interleukin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

48
785
6
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 644 publications
(843 citation statements)
references
References 49 publications
48
785
6
4
Order By: Relevance
“…6D). Finally, we assessed whether IL-22 single-positive cells generated in vitro from naïve T cells expressed CD161, a marker reported to be specific of Th17 cells [9,36]. Our results confirm the strong expression of CD161 by most IL-17 1 IL-22 À IFN-g À cells but also show that CD161 is virtually absent from IL-22 1 IL-17A À IFN-g À single-positive T cells (Fig.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…6D). Finally, we assessed whether IL-22 single-positive cells generated in vitro from naïve T cells expressed CD161, a marker reported to be specific of Th17 cells [9,36]. Our results confirm the strong expression of CD161 by most IL-17 1 IL-22 À IFN-g À cells but also show that CD161 is virtually absent from IL-22 1 IL-17A À IFN-g À single-positive T cells (Fig.…”
supporting
confidence: 70%
“…Fifth, priming of CD4 1 naïve T cells in the presence of TCDD resulted in increased number of IL-22 1 IL-17 À IFN-g À single-positive T cells. Finally, CD161 selectively expressed in Th17 cells [9,36] was absent in IL-22 1 IL-17A À IFN-g À singlepositive T cells. Furthermore, our data regarding the dissociated IL-22 and IL-17 production are consistent with recent reports showing that skin-homing memory T cells [31,32], T cells present in the skin of individuals affected by atopic dermatitis [41], plaque psoriasis, allergic contact dermatitis [33] and T cells responding to mycobacteria [42] or Candida albicans [43] produce IL-22 but not IL-17A or IFN-g. Of interest, human Langerhans cells appear to favor the induction of CD4 1 T cells producing IL-22 but not IL-17, thus stressing a preferential role of these cells in skin immunosurveillance [44].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…76 CD161 expression by T lymphocytes has also been linked to their capacity to secrete IL-17A. 77 MDR1 expression might therefore be required for their proper function and to preserve them from toxins and xenobiotics particularly abundant in the intestine. In this matter, a recent work from Cao et al .…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown that virtually all human memory Th17 cells are contained within the CD161 + fraction of both circulating and tissue-infiltrating CD4 + T cells, and originate from CD161 + precursors present in umbilical cord blood and newborn thymus [9]. In humans, Th1 cells that derive from the shifting of Th17 cells have been defined as nonclassic Th1 cells [8,10], since they can be distinguished from classic Th1 cells by the expression of CD161, as expressed by Th17 cells [9][10][11].More recently, we have demonstrated that Th17 cells, unlike classic Th1 cells, do not proliferate in response to anti-CD3 plus anti-CD28 mAb stimulation; this unresponsiveness is due mainly to the inability of human Th17 cells to produce IL-2, which could be related to their reduced c-Fos, c-Jun, and NFAT activity [12]. Moreover, we found that the reduced activity of these transcription factors is associated with high expression of IL-4-induced gene 1 (IL4I1) mRNA, which encodes an L-phenylalanine oxidase able to downregulate the expression of CD3 chains in T cells, thus resulting in a poor ability to expand in response to TCR stimulation [12].…”
mentioning
confidence: 96%